Utero-ovarian ligament fibroid-an unusual location of extrauterine fibroids - Saini, Arunima; Gothwal, Meenakshi; Singh, Pratibha; Yadav, Garima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Utero-ovarian ligament fibroids are among the rarest sites for extrauterine leiomyomas. Broad ligament fibroids are relatively common. They can be either asymptomatic or present with chronic pelvic pain and pressure symptoms. They can be confused with an ovarian mass, broad ligament cyst or a pedunculated fibroid. There are high chances of missing it clinically. Ultrasonography, magnetic resonance imaging (MRI) and computed tomography scan are the imaging techniques used to diagnose such conditions, MRI being the most accurate in ruling out other broad ligament masses with suspected ovarian, tubal or isolated broad ligament cyst. Here is a rare case report of a pedunculated extrauterine leiomyoma with its origin in the utero-ovarian ligament.